Analisis Makna Pesan Kata Genji Pada Film Crows Zero - Muhammad Nur Zikirullah; Taufiq Furqon Nurhakim (Lembaga Pengembangan Kinerja Dosen, 2025)
Film plays a significant role in shaping perceptions and behaviors, particularly among adolescents. Action films with themes of teenage life and inter-gang fights, such as Crows Zero, are compelling to watch and have the potential to be a source of inspiration. This study aims to analyze the meaning of the messages contained in the film Crows Zero, focusing on understanding that the name